(untitled) (International Journal of Engineering and Computer Science, 2014)
Communication is the important part in any type of network for making it possible to transfer data from one node to another. Communication needs quality and security for better performance and for acceptance of users and client companies. Quality is dependent on size and some other factors of network but security is very concern parameter in network as it is independent of network size and complexity. Security has become more important to personal computer users, organizations, and the military. Security became a major concern with the advent of internet and the history of security allows a better understanding of the emergence of security technology. The internet structure itself allowed for many security threats to occur. The modified architecture of the internet can reduce the possible attacks that can be sent across the network. Knowing the attack methods, allows for the appropriate security to emerge. Data integrity is quite a issue in security and to maintain that integrity we tends to improve as to provides the better encryption processes for security. In our proposed work we provide harder encryption with enhanced public key encryption protocol for security and proposed work can be implemented into any network to provide better security. We have enhanced the hardness in security by improving the Diffie-Hellman encryption algorithm by adding some more security codes in current algorithm.